Fundamentals of Arterial Blood Gas Interpretation. Issue 8 (25th August 2022) - Yee, Jerry; Frinak, Stan; Mohiuddin, Naushaba; Uduman, Junior
Abstract : Acid-base disturbances in patients with cardiopulmonary or other disorders are common and are often misinterpreted or interpreted incompletely. Treating acid-base disorders in greater detail facilitates pathophysiologic understanding and improved therapeutic planning. Understanding the ratiometric relationship between the lungs, which excrete volatile acid as carbon dioxide, and the kidneys, which contribute to maintenance of plasma bicarbonate, allows precise identification of the dominant acid-base disturbance when more than a simple disorder is present and aids in executing a measured treatment response. Concordantly, mapping paired values of the partial pressure of carbon dioxide (PCO2 ) and the bicarbonate concentration ([HCO3 – ]) on a Cartesian coordinate system visually defines an acid-base disorder and validates the ratiometric methodology. We review and demonstrate the algebraic and logarithmic methods of arterial blood gas analysis through the example of a complex acid-base disorder, emphasizing examination of the PCO2 -to-[HCO3 – ] ratio.